a) Viết lại phương trình thành y = 3 – 2x . Từ đó, tất cả các nghiệm đã cho được biểu diễn bởi đường thẳng d: y = 3 – 2x.
b) Viết lại phương trình thành y = 3 . Từ đó, tất cả các nghiệm đã cho được biểu diễn bởi đường thẳng d: y = 3.
c) Viết lại phương trình thành x = \(\frac{{ - 2}}{3}\) . Từ đó, tất cả các nghiệm đã cho được biểu diễn bởi đường thẳng d: x = \(\frac{{ - 2}}{3}\).
d) Viết lại phương trình thành y = 2x . Từ đó, tất cả các nghiệm đã cho được biểu diễn bởi đường thẳng d: y = 2x.
Đúng 0
Bình luận (0)